Infertility treatment associated with childhood asthma and atopy. Issue 7 (21st April 2022) - Polinski, Kristen J; Stevens, Danielle R; Mendola, Pauline; Lin, Tzu-Chun; Sundaram, Rajeshwari; Bell, Erin; Yeung, Edwina H
Abstract: STUDY QUESTION: Are children who were conceived with infertility treatment at an increased risk of developing asthma and atopic conditions? SUMMARY ANSWER: Infertility treatment is associated with an elevated risk of asthma and atopic conditions in early and middle childhood, even after adjustment for parental asthma and atopy. WHAT IS KNOWN ALREADY: Asthma and atopic conditions are prevalent in childhood. The development of these conditions may be linked to early life exposures, including the use of infertility treatments. STUDY DESIGN, SIZE, DURATION: Upstate KIDS is a prospective cohort study of singletons and multiples born between 2008 and 2010. A total of 5034 mothers and 6171 children were enrolled and followed up until 2019, and 2056 children participated in the middle childhood follow-up. PARTICIPANTS/MATERIALS, SETTING, METHODS: Women reported the fertility agents used to become pregnant on a baseline questionnaire. Treatment was categorized as ART (∼22%) use, ovulation induction via oral/injectable medications with or without IUI (OI/IUI, ∼20%), or no treatment (∼58%). Outcomes were assessed by maternal report on questionnaires in early (up to age 3 years, prevalence 9–28%) and middle (7–9 years, prevalence 10–16%) childhood. Weighted Poisson regression models with robust standard errors were used to analyze the risk of atopic outcomes in relation to infertility treatment exposure. MAIN RESULTS AND THE ROLE OF CHANCE: Compared to children conceived without treatment, children conceived with any infertility treatment were at an increased risk of persistent wheeze by age 3 years (relative risk (RR): 1.66; 95% CI: 1.17, 2.33) with adjustments for parental atopy among other risk factors. Around 7–9 years, children conceived with treatment were more likely to have current asthma (RR: 1.30; 95% CI: 0.98, 1.71), eczema (RR: 1.77; 95% CI: 1.25, 2.49) or be prescribed allergy-related medications (RR: 1.45; 95% CI: 1.06, 1.99). Similar effect sizes were found when examining associations by treatment type (i.e. ART versus OI/IUI). LIMITATIONS, REASONS FOR CAUTION: Childhood outcomes were based on maternal report and are subject to potential misclassification. There was attrition in this study, which limits the precision of our measures of association. WIDER IMPLICATIONS OF THE FINDINGS: Though future research is needed to clarify the mechanisms involved, our findings support that both ART and OI/IUI influences the development of asthma and atopic conditions in the offspring from an early age. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by the National Institutes of Health's Intramural Research Program at the Eunice Kennedy Shriver National Institute of Child Health and Human Development (NICHD; contracts #HHSN275201200005C, #HHSN267200700019C, #HHSN275201400013C, #HHSN275201300026I/27500004, #HHSN275201300023I/27500017). The authors have no relevant conflicts of interest to disclose. TRIAL REGISTRATION NUMBER : N/A